Aggressive vertebral hemangioma in early adolescent age group: Atypical presentation with computed tomography and magnetic resonance imaging appearance - Sharma, B B; Sharma, Shashi; Sharma, Sandeep; Balesa, Jitendra; Jilowa, Sarita; Singh, Yashvant (Indian Journal of Child Health, 2015)
Vertebral hemangiomas (VH) are vertebral vascular malformations, which may remain asymptomatic until adulthood. Sometimes, young individuals present with unexplained backache, which poses the diagnostic dilemma. We present a case of 15-year-old female who presented with prolonged unexplained intermittent upper back pain in the dorsal region. She was diagnosed as a case of aggressive VH after ruling out other infective and malignant pathologies and treated with decompressive therapy. The present case highlights the role of imaging studies such as computed tomography and magnetic resonance imaging in such conditions.